Gaming disorder test: Assessing psychometric properties, prevalence, temporal stability, and invariance using a Czech two-time-point longitudinal sample - Siřínková, Dita; Blinka, Lukas; Montag, Christian (Journal of psychiatric research, 2024)
In 2019, Gaming Disorder (GD) was acknowledged as an official diagnosis by the World Health Organization. The Gaming Disorder Test (GDT) is the most widely used tool to measure GD; however, due to its novelty, various measurement properties are still unexplored, and the number of validated language variants is still limited. The present study is the first to assess the psychometric properties of the Czech version of the GDT. Further, it focuses on its temporal prevalence and stability, gaming genre invariance, and criterion validity. A large-scale sample of adult Czech gamers collected at two points within nine months was analysed - T1 N = 5356; T2 N = 6077; longitudinal sample N = 1430. Confirmatory factor analysis (CFA), structural equation modelling (SEM), and multigroup CFA were employed to assess the measurement invariance. The study confirmed the one-factor structure of the GDT and showed that it is invariant across preferred gaming genres and the time of data collection. It showed a negative relationship with life satisfaction and a positive relationship with anxiety, even when controlling for their mutual relationships. The prevalence in the longitudinal sample was equal to or below 1.9% in each wave, but only 0.5% in the longitudinal sample (hence n = 7 participants fulfilled in both waves the criteria for GD). The study suggests that the Czech version of the GDT has good psychometric properties, including temporal stability and invariance across gaming genres, so it is suitable for the survey type and epidemiological investigation of the ICD-11's Gaming Disorder.
Keywords: Humans; Longitudinal Studies; Internet Addiction Disorder; lidé středního věku; Longitudinal investigation; prevalence; Female; mladý dospělý; dospělí; Psychiatric Status Rating Scales; lidé; Measurement invariance; reprodukovatelnost výsledků; Gaming disorder; Adult; ženské pohlaví; longitudinální studie; psychiatrické posuzovací škály; Male; Reproducibility of Results; Middle Aged; Adolescent; Psychometrics; Validation; Czech Republic; Young Adult; Prevalence; netholismus; Gaming disorder test; Česká republika; mužské pohlaví; psychometrie; mladiství